KOMUNIKASI INTERPERSONAL ORANG TUA DALAM PEMBINAAN KARAKTER RELIGIUS REMAJA DI KELURAHAN BUNGI KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Fatmin; Nur Setiawati; Nengsi, Ratika; Hasriani, Andi; Sudarmono , Muh. Aidil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and describe the patterns of interpersonal communication employed by parents in developing the religious character of adolescents in Bungi Village, Bungku Tengah District, Morowali Regency. Effective interpersonal communication between parents and adolescents constitutes one of the key factors in shaping religious character among the younger generation, particularly amid the growing influence of external cultures and the rapid advancement of information technology. This research employed a descriptive qualitative approach utilizing in-depth interviews, observation, and documentation as data collection techniques. Research subjects consisted of parents and adolescents residing in Bungi Village. Data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings revealed that parents' interpersonal communication in Bungi Village is conducted through dialogic approaches, role-modeling, and continuous supervision. Communication patterns applied include verbal communication in the form of advice, motivation, and discussions of religious values, as well as nonverbal communication through parents' daily attitudes and behaviors. The development of adolescents' religious character encompasses the instillation of worship values, noble morals, and social responsibility based on Islamic teachings. Supporting factors include a harmonious family environment and active participation in religious activities within the community, while inhibiting factors include the influence of social media and free association that tend to erode adolescents' religious values. This study concludes that warm, open, and consistent interpersonal communication between parents and adolescents plays a significant role in building strong religious character. Synergy among family, school, and society is required to create a conducive ecosystem for the development of adolescents' religious character.